Perspectives of Manufacturing Subsidiaries of Foreign Companies in Russia: Frontier, Faubourg or Sticks? - Igor' Gurkov; Evgeniy Morgunov; Zokirzhon Saidov; Aleksandr Arshavskiy (Foresight and STI Governance)
We present the dynamics of the position of Russian manufacturing subsidiaries of Western MNCs in 2012–2016. The analysis is based on interviews with the heads of subsidiaries, a repeated survey of plant managers and on secondary data on subsidiaries’ activities. We propose a new portfolio model that desalinates “the core” and “the periphery” of the corporation and further allocates peripheral subsidiaries into several classes depending on intensity of value transfer from and to a subsidiary and the possibility to apply a “standard” set of instruments for capital allocation decisions. We argue that in the current situation of the Russian economy the only possibility for Russian manufacturing subsidiaries to remain close to the corporate core is to demonstrate high net profitability of assets. Otherwise subsidiaries are downgraded into “sticks”. That position enables subsidiary managers to enjoy high autonomy and wide subsidiary mandates, but endanger the long-term perspectives on maintaining innovativeness and competitiveness of subsidiaries.